Políticas públicas voltadas à população em situação de rua na cidade de São Paulo: uma análise sobre o segmento LGBTT que vive na a rua - Salgueiro, Flávio Soares Correia (2020)
Living on the street today is one of the biggest social problems, which is why it is very important to promote studies that lead us to know more deeply the picture of extreme social exclusion, experienced by countless people. In this sense, the present work arose from the interest of studying the LGBTT segment that lives in the streets and it is extreme vulnerable, who suffers various types of violence, mainly that of the stigma to which they are subject, including by the population that lives on the streets of São Paulo. The goal is to know this group more closely, to identify and analyze the effectiveness of existing public policies focused on this social segment and the access to them. For this reason, a qualitative research was conducted, through semi-structured interviews, with users of some services analyzed, members of the LGBTT population, who were on the street at the time of the survey